In the face of adversity: Resiliency in winter sport athletes - Brown, H. E.; Lafferty, M. E.; Triggs, C. (Science & Sports, 2015)
Objectives: To explore winter sports athletes` experiences of adversity within their sporting careers. Methods: Data were collected from semi-structured interviews with seven British elite winter sports athletes (mean age = 23.1 years, S.D. = 2.4), representing a range of winter sport disciplines. Results: Twelve general dimensions emerged, serving to support the pioneering conceptual model of sport resilience, and emphasizing the role previous experiences of adversity have on the acquisition of resilient qualities. Conclusions: The findings from this study have the potential to inform applied sport psychology practice. Specifically regarding the development of a `resiliency package`, which could aim to protect athletes from maladaptive and/or dysfunctional responses to adversity, and encourage adaptive and resilient reintegration.